An Indirect-Effects Model of Mediated Adjudication: The CSI Myth, the Tech Effect, and Metropolitan Jurors' Expectations for Scientific Evidence - Barak, Gregg (2009)
Part I of this article defines the CSI effect, a phrase has come to have many different meanings ascribed to it. It emphasizes the epistemological importance of first describing the effect of the CSI effect as observed in juror behavior documented in a new study conducted in Wayne County (Detroit), Michigan, and then looking at causative factors that may be related to an explanation of those observed effects. Part II describes the methodology of the Wayne County study, provides a descriptive analysis of Wayne County jurors, and compares the jurors demographically to the Washtenaw County jurors who were surveyed in 2006. Part III analyzes the Wayne County study results with respect to jurors' expectations and demands for scientific evidence. The Wayne County study findings reinforce the earlier Washtenaw findings of heightened juror expectations and demands for scientific evidence in almost every respect. This most recent analysis reinforces conclusions from the earlier study that there is no such causative relationship between watching CSI and heightened juror expectations and demands. Part IV explores the nature of the tech effect as one causative factor for those heightened juror expectations and demands as an alternative to the CSI effect. The results of regression analyses of new data provide some support for the 2006 study's suggestion of a tech effect --that the broader changes in popular culture brought about by rapid scientific and technological advances and widespread dissemination of information about them is a more likely explanation for increased juror expectations and demand for scientific evidence. Part V provides an overview of contemporary perspectives of mass-mediated effects on public attitudes, behaviors, and expectations as a prelude to a suggested Indirect-Effects Model of Mediated Adjudication. The authors propose an indirect-effects model of juror influences that triangulates the potential interactive effects of a CSI effect myth with the likelihood of a tech effect in the context of the mass mediated effects of law and order or crime and justice news media